2016
DOI: 10.1186/s12917-015-0631-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and temporospatial gait parameters in a heterogeneous group of dogs

Abstract: BackgroundA prime concern of the gait analysis in a heterogeneous group of dogs is the potential influence of factors such as individual body size, body mass, type of gait, and velocity. Thus, this study aimed to evaluate in a heterogeneous group of dogs a possible correlation of the stride frequency with kinetic and temporospatial variables, as well as the percentage of body weight distribution (%BWD), and compare symmetry index (SI) between trotting and walking dogs. Twenty-nine clinically healthy dogs movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 22 publications
6
50
1
Order By: Relevance
“…Body mass distribution in pigs (Meijer et al, 2014) and other animals is approximately 30% on each front limb and 20% on each hind limb (Besancon et al, 2004;Budsberg et al, 1987;Kim and Breur, 2008;Kano et al, 2016). In line with this, Thorup et al (2007) showed 54% of body mass is carried by the pig's forelimbs, which demonstrates that the centre of gravity is relatively close to the forelimbs.…”
Section: Does Intralimb Coordination Differ As a Function Of Body Build?supporting
confidence: 49%
“…Body mass distribution in pigs (Meijer et al, 2014) and other animals is approximately 30% on each front limb and 20% on each hind limb (Besancon et al, 2004;Budsberg et al, 1987;Kim and Breur, 2008;Kano et al, 2016). In line with this, Thorup et al (2007) showed 54% of body mass is carried by the pig's forelimbs, which demonstrates that the centre of gravity is relatively close to the forelimbs.…”
Section: Does Intralimb Coordination Differ As a Function Of Body Build?supporting
confidence: 49%
“…The percentages of stance and swing phases in our study are comparable to those previously reported . However, the relative duration of stance and swing phases can vary slightly between studies.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, a 3D kinematic camera system and a retroreflective toe marker were used to document the initiation and termination of the stance and swing phases, and produce temporospatial variables . This design differs from previous studies, where treadmill embedded force plates, pressure walkways, and high‐speed optical video recordings have been utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, functional assessments started to be considered in many different animal models like rats, for stroke model [7], for peripheral nerve injury [8,11] and others [54], dogs [53,55] and minipigs [56].…”
Section: Discussionmentioning
confidence: 99%